2016
DOI: 10.1634/theoncologist.2015-0497
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Genomic Profiling Identifies a Subset of Crizotinib-Responsive ALK-Rearranged Non-Small Cell Lung Cancer Not Detected by Fluorescence In Situ Hybridization

Abstract: Introduction. For patients with non-small cell lung cancer (NSCLC) tobenefitfromALKinhibitors,sensitiveandspecificdetectionofALK genomic rearrangements is needed. ALK break-apart fluorescence in situ hybridization (FISH) is the U.S. Food and Drug Administration approved and standard-of-care diagnostic assay, but identification of ALK rearrangements by other methods reported in NSCLC cases that tested negative for ALK rearrangements by FISH suggests a significant false-negative rate. We report here a large seri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
96
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 16 publications
2
96
0
Order By: Relevance
“…Consistent with our finding, a recent tissue-based study reported a FISH false negative rate of 35% in a cohort of 47 patients who were found to be ALK positive by NGS, suggesting that NGS-based assessment for ALK fusions may be warranted in patients with higher probability of ALK fusion and whose FISH analysis is negative. 34 The importance of this is illustrated by three patients in our cohort who, despite a negative ALK FISH were ALK positive by cfDNA and went on to respond to ALKi treatment. Clinical data was not available for the remaining two tissue–negative but cfDNA–positive ALK fusion patients.…”
Section: Discussionmentioning
confidence: 89%
“…Consistent with our finding, a recent tissue-based study reported a FISH false negative rate of 35% in a cohort of 47 patients who were found to be ALK positive by NGS, suggesting that NGS-based assessment for ALK fusions may be warranted in patients with higher probability of ALK fusion and whose FISH analysis is negative. 34 The importance of this is illustrated by three patients in our cohort who, despite a negative ALK FISH were ALK positive by cfDNA and went on to respond to ALKi treatment. Clinical data was not available for the remaining two tissue–negative but cfDNA–positive ALK fusion patients.…”
Section: Discussionmentioning
confidence: 89%
“…[65][66][67][68][69][70][71][72][73][74] NGS can also be used to assess whether ALK rearrangements are present, if the platform has been appropriately designed and validated to detect ALK rearrangements. [75][76][77] Crizotinib-an inhibitor of ALK, ROS1, and some MET tyrosine kinases (high-level MET amplification or MET exon 14 skipping mutation)-is FDA-approved for patients with locally advanced or metastatic NSCLC who have ALK gene rearrangements (ie, ALK-positive disease) or ROS1 rearrangements. [78][79][80][81][82][83][84][85] Crizotinib yields very high response rates (>60%) when used in patients with advanced NSCLC who have ALK rearrangements, including those with brain metastases.…”
Section: Alk Gene Rearrangementsmentioning
confidence: 99%
“…Of key interest, in our study nCounter allowed to identify 10 ALK-positive cases for fusion genes that were qualified as negative by FISH [8]. In this respect, there is growing evidence that new molecular platforms with NGS techniques are more sensitive than FISH in detecting ALK rearrangements [8,10,11].…”
mentioning
confidence: 90%